FORECAST OF VEHICLE PRODUCTION IN BRAZIL USING ZHANG’S HYBRID MODEL - Júnior, Arundo Nunes da Silva (Seven Editora, 2024)
This study presents the application of Zhang’s hybrid model to predict vehicle production in Brazil. The model combines wavelets, ARIMA, and LSTM neural network techniques to provide more accurate and robust predictions. The results demonstrate the effectiveness of the proposed model, highlighting its application in planning and decision-making in the automotive sector. DOI:https://doi.org/10.56238/sevened2024.037-045